Implementasi Kebijakan Pembangunan Manusia di BAPPEDA Kabupaten Dairi Studi Pengalaman Magang Mandiri - Stela Sri Rejeki Purba; Elvis F. Purba (PADMA, 2025)
This paper aims to describe the implementation of human development policies at the Regional Development Planning Agency (Bappeda) of Dairi Regency through an independent internship experience. Human development is a multidimensional approach that emphasizes improving the quality of health, education, and social welfare as key indicators of regional progress. This paper uses a descriptive qualitative approach with participatory observation techniques, activity documentation, and direct involvement in policy planning and coordination activities. The results of the discussion indicate that the implementation of human development policies in Dairi Regency is carried out through internal bureaucratic coordination, cross-sectoral collaboration to accelerate stunting reduction, empower women and protect children, and strengthen population data-based planning. The role of Bappeda as a strategic coordinator is crucial for the effectiveness of policy integration. Although implementation has been systematic, strengthening data integration and ongoing monitoring are still needed to sustainably improve the quality of human development.